The Effects of Government Education Spending on School Enrollment in Indonesia - Megawati Megawati (Universitas Batanghari Jambi, 2020)
Government expenditure for education increases every year for the implementation of education sector including to increase the number of enrollment rate. However, there are some children who do not enroll in school especially senior high school-aged children. This study examines the effects of government spending on education on school enrollment in Indonesia. This research uses cross-sectional data from the National Socioeconomic Survey (Susenas) and the government spending on education data for four years. This study uses probit model by employing the government education spending as the main factor. The control variables used in this study consist of parents’ education, household expenditure, male, urban, birth order, the number of siblings, missing parent, GRDP per capita, year dummy, and interaction terms among some variables. The observation is divided into two groups of age: 7-15 and 16-18. The results show that the government education spending has a positive and significant effect on school enrollment in Indonesia. In addition, the interaction terms show that the government education spending is associated with greater probability of school enrollment for poor children and for the girls.